On the move to meaningful internet systems: OTM 2011 Confederated International Conferences: CoopIS, DOA-SVI, and ODBASE 2011, Hersonissos, Crete, Greece, October 17-21, 2011, Proceedings, Part I - Meersman, Robert (Lecture Notes in Computer Science, 2011)
The two-volume set LNCS 7044 and 7045 constitutes the refereed proceedings of three confederated international conferences: Cooperative Information Systems (CoopIS 2011), Distributed Objects and Applications - Secure Virtual Infrastructures (DOA-SVI 2011), and Ontologies, DataBases and Applications of SEmantics (ODBASE 2011) held as part of OTM 2011 in October 2011 in Hersonissos on the island of Crete, Greece. The 55 revised full papers presented were carefully reviewed and selected from a total of 141 submissions. The 27 papers included in the first volume constitute the proceedings of CoopIS 2011 and are organized in topical sections on business process repositories, business process compliance and risk management, service orchestration and workflows, intelligent information systems and distributed agent systems, emerging trends in business process support, techniques for building cooperative information systems, security and privacy in collaborative applications, and data and information management.